OFFLINE TRAVEL IN AN ONLINE WORLD: SOCIAL, ECONOMIC, AND PSYCHOLOGICAL IMPACTS OF ANALOGUE TOURISM IN THE DIGITAL ERA - I Nengah Suardhana; I Wayan Kartimin; I Gusti Bagus Rai Utama (Bajang Institute, 2026)
This study examines the persistence and implications of offline travel within an increasingly digital tourism ecosystem dominated by online travel agencies, algorithmic recommendation systems, and mobile applications. It adopts a mixed-methods design involving semi-structured interviews with foreign tourists in Bali, an online survey, and secondary data from industry reports and destination case studies to explore social, economic, and psychological dimensions of analogue travel practices. Findings indicate that offline travel is sustained by quests for authenticity, deeper interpersonal interactions, and digital detox benefits, yet is constrained by convenience gaps, perceived inefficiency, and fear of missing out among younger, highly connected segments. Economically, offline channels continue to support micro, small, and medium enterprises, homestays, and local guides, particularly in rural and digitally excluded areas, but face intense price competition and visibility disadvantages relative to OTAs. Psychologically, offline travel enhances autonomy, self-efficacy, and attentional restoration, while simultaneously generating frustration for tourists accustomed to seamless digital services. The study contributes to tourism scholarship by clarifying the underexplored interplay between online and offline travel experiences and offers practical insights for policymakers and businesses seeking to design more balanced, human-centred tourism futures.